Teacher Evaluation - a Systemic Challenge: Array - Stanciu, Filip; Tureac, Cornelia Elena; Stanciu, Lidia; Enache, Sorin (Didactica Danubiensis, 2022)
Improving the teacher evaluation process is a necessary and beneficial measure for all participants in the education system. Therefore, teacher evaluation is a key element in quality assurance and performance. Therefore, concrete efforts must be made to encourage the participation of all stakeholders in the evaluation of teachers. The model for the evaluation of pre-university teachers is based on: the results obtained from quantitative research, on the analysis of current trends in Romanian and European pre-university education and the analysis of the legislative framework of evaluation.